Pengaruh Kecerdasan Emosional Kemampuan dan Motivasi Kerja Terhadap Kinerja Pegawai di Kantor Badan Perencanaan Pembangunan, Penelitian dan Pengembangan - Tengku Aulia Rahman; Sandi Suhendri; Rudy Rinaldi; Muhammad Ramzi; Erizal Lubis; Gustina Pane (Journal of Trends Economics and Accounting Research, 2023)
There is a positive and significant influence of Emotional Intelligence on the Performance of the Regional Planning, Development, Research and Development Office (BAPPEDA) of Aceh Tamiang Regency of 0.343 on Employee Performance so that it can be concluded that adequate Emotional Intelligence can determine Employee Performance will also be high even though there are other variables that support to see the results of an employee's performance. There is a positive but not significant influence on the performance of the Office of Planning, Development, Research and Regional Development (BAPPEDA) of Aceh Tamiang Regency of 0.222 on employee performance so that it can be concluded that adequate ability can determine employee performance will also be high even though there are other variables that support for see the results of an employee's performance. There is a positive but not significant effect of work motivation on employee performance at the Regional Planning, Development, Research and Development Office (BAPPEDA) of Aceh Tamiang Regency of 0.047 on employee performance so that it can be concluded that adequate work motivation can determine employee performance as well will be low even though there are other variables that support to see the results of an employee's performance. Simultaneously, it can be seen that the independent variables of Emotional Intelligence, Ability and Work Motivation have a significant value (0.000 < 0.05 and fcount > ftable (9,529 > 3.15). So it can be concluded that the variables of Emotional Intelligence, Ability and Work Motivation have an effect significantly and simultaneously on employee performance, so this means that the higher the emotional intelligence, ability and work motivation, the better the employee performance, and conversely, the lower the emotional intelligence, ability and work motivation, the employee's performance is getting less good.